A Survey on Green Computing Based on Cloud Environment - Zhao, Jia; Hu, Liang; Xu, Gaochao; Ding, Yan; Chu, Jianfeng (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Cloud computing and virtualization have become research hotspots in recent years. Since information communication technology is widely used in real life, data centers have rapidly been developed and the number of data centers has increased a lot. However, the existing data centers have too much power consumption. The energy and resources utilization are much lower. Against this backdrop, green computing is proposed. This paper briefly introduces some technologies based on computer system and cloud computing aimed at energy efficiency without compromising the performance objectives. Finally, the future research trends are analyzed.